Brown tumour mimicking skeletal metastasis. Issue 7 (13th July 2021) - Parikh, Pankti; Shetty, Sahana; Rodrigues, Gabriel; Bhat, Shyamasunder N
Abstract : Brown tumours of bone are highly vascular osteolytic lesions that depict a reparative cellular process instead of a neoplastic process in hyperparathyroidism (HPT) patients. These tumours have the potential to be aggressive and destructive. We report a case of a 30-year-old woman who presented with left thigh and lower back pain. The radiological evaluation showed multiple bony lesions in the pelvis and the spine, which mimicked multiple metastatic tumours. However, on biochemistry evaluation, serum calcium, alkaline phosphatase, and parathyroid hormone were all high, while serum phosphate was low, indicating primary HPT (PHPT), which was confirmed by parathyroid scintigraphy showing left parathyroid adenoma. Hence, the bony lesions were diagnosed as brown tumours secondary to PHPT. The patient underwent parathyroidectomy and developed severe hungry bone syndrome requiring parenteral calcium infusion along with oral calcium and active vitamin D supplementation. The clinical symptoms of bone pain improved after surgery.